Model output associated with "Sensitivity of convective self-aggregation to domain size" - Patrizio, Casey R.; Randall, David A. (Colorado State University. Libraries, 2019)
A 3D cloud-resolving model has been used to investigate the domain-size-dependence of simulations of convective self-aggregation (CSA) in radiative--convective equilibrium. We investigate how large a domain is needed to allow multiple convective clusters, and also how the properties equilibrated CSA depend on domain size. We used doubly-periodic square domains of widths 768 km, 1536 km, 3072 km and 6144 km, over 350 simulated days. In the 768 km, 1536 km, and 3072 km domains, the simulations produced circular convective clusters surrounded by broader regions of dry, subsiding air. In the 6144 km domain, the convection ultimately forms two disconnected bands. As the domain size increases, equilibrated CSA moistens in two ways. First, as the circulation widens, this leads to stronger boundary layer winds and a more humid boundary-layer. Second, the stronger inflow into the convective region boundary-layer (CBL) is associated with a warmer CBL, which leads to intensified deep convection, more melting and freezing near the freezing level, enhanced mid-level stability, increased congestus activity and detrainment of moist air into the dry region. In the larger domains, the deep convection and congestus slowly oscillate out of phase with each other with a time period of about 25 to 30 days. We hypothesize that other important domain-size sensitivities, including a decrease in net MSE export from the convective region, are fundamentally linked to the increasing relationship between domain size and boundary-layer wind speed. Our results suggest that the statistics of CSA converge only for domains wider than about 3000 km.
The following model output is a subset of the data used to produce the figures in "Sensitivity of Convective Self-Aggregation to Domain Size". Full model output can be obtained by contacting casey.patrizio@colostate.edu. The model output is from simulations of radiative-convective equilibrium using the cloud-resolving model, the System for Atmospheric Modeling (SAM). Four different square-domain sizes are used: S (768 x 768 km), M (1536 x 1536 km), L (3072 x 3072 km) and XL (6144 x 6144 km) with a horizontal grid spacing of 3 km and 64 vertical levels, over a maximum time of 350 simulated days. Hourly mean statistics are included in the subdirectory OUT_STAT, and hourly 2D fields are included in the subdirectory OUT_2D. Six-hourly 3D fields are included in the subdirectory OUT_3D. encompassing hourly mean statistics for all 4 domains over the entire simulation, 2D fields for the S, M and L domains over the entire simulation, and 3D fields for the S, M, L and XL domains near the end of simulation. File names have the following format: _____.nc. For example, "STAT_256x256x64_3000m_10s_250days_302K.nc" corresponds to hourly mean statistics for the S domain, with a time step of 10 seconds over 250 simulated days and a sea-surface temperature of 302K. More details about the variables contained in each file can be found by using the command 'ncdump -h '.
Department of Atmospheric Science
Keywords: atmospheric sciences; radiative-convective equilibrium; convective self-aggregation